1996
DOI: 10.1074/jbc.271.38.22953
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of p38 Mitogen-activated Protein Kinase Activity by Phosphorylated Glia Maturation Factor

Abstract: We previously demonstrated that glia maturation factor (GMF), a 17-kDa brain protein, can be phosphorylated in test tube by several protein kinases, and that endogenous GMF is rapidly phosphorylated upon stimulation of astrocytes by phorbol 12-myristate 13-acetate. We further observed that protein kinase A (PKA)-phosphorylated GMF is a potent inhibitor (IC50 = 3 nM) of the ERK1/ERK2 (p44/p42) subfamily of mitogen-activated protein (MAP) kinase. We now report that, by contrast, PKA-phosphorylated GMF strongly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 24 publications
4
59
0
Order By: Relevance
“…4 shows that there were at least three defined protein bands capable of phosphorylating GMF, two of which were identical in electrophoretic mobility with PKA and PKC, whereas a third band was unidentified. Although the results may not necessarily reflect the in vivo situation, when taken together with our earlier findings that phorbol ester (activator of PKC) and forskolin (activator of PKA) stimulate the phosphorylation of endogenous GMF in live cells (4,6), a strong argument can be made for the activation of endogenous GMF by endogenous PKC and PKA.…”
Section: Figmentioning
confidence: 54%
See 1 more Smart Citation
“…4 shows that there were at least three defined protein bands capable of phosphorylating GMF, two of which were identical in electrophoretic mobility with PKA and PKC, whereas a third band was unidentified. Although the results may not necessarily reflect the in vivo situation, when taken together with our earlier findings that phorbol ester (activator of PKC) and forskolin (activator of PKA) stimulate the phosphorylation of endogenous GMF in live cells (4,6), a strong argument can be made for the activation of endogenous GMF by endogenous PKC and PKA.…”
Section: Figmentioning
confidence: 54%
“…Thus, it is possible that various phosphorylated isoforms of GMF may be generated inside the cell by kinases differentially stimulated by external stimuli. Although no isoform of GMF, phosphorylated or nonphosphorylated, possesses kinase or phosphatase activity (4,5), we have shown recently that PKAphosphorylated GMF is a potent inhibitor of ERK (5) and also an enhancer of p38 (6); both are subfamilies of MAP kinase, suggesting that GMF is a bifunctional regulator of the MAP kinase cascades. To find out any additional locations where GMF can regulate, we have tested the effect of GMF and GMF-P on PKA.…”
Section: Glia Maturation Factor (Gmf)mentioning
confidence: 96%
“…Microarray analysis showed that PKCi depletion increased the levels of glia maturation factor b (GMFb), a protein which has previously shown to be an enhancer of p38 MAP kinase signaling ( Figure 5B) (Lim and Zaheer, 1996). This suggested that PKCi could protect cells from apoptosis by preventing GMFb-mediated enhancement of p38 MAP kinase signaling.…”
Section: Pkci Represses Glia Maturation Factor B Expressionmentioning
confidence: 79%
“…This beneficial effect comes at a price, as GMFb sensitizes both astrocytes and proximal tubular kidney cells to oxidative injury (Kaimori et al, 2003;Zaheer et al, 2004). At least part of this sensitization is due to GMFb's ability to enhance p38 MAP kinase activity (Kaimori et al, 2003;Zaheer et al, 2004), which appears to involve a physical association between GMFb and this kinase in cells (Lim and Zaheer, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation